Photothermal and Electrical Characterization of Zno-Based Varistor Systems - Rizwan, Zahid (2007)
Photopyroelectric spectroscopy is a powerful tool for examining the optical properties related to non-radiative de-excitation processes in materials. This technique consists of using a thin photopyroelectric (PPE) film in intimate contact with a solid sample on which modulated monochromatic light beam is incident. The non-radiative de-excitation process within the solid causes the sample temperature to fluctuate and PPE signal is produced in PPE transducer as a result of this temperature fluctuation. Varistor is a voltage dependant resistor and is used as a protective device to regulate transient voltage surges of unwanted magnitudes caused by lightning and switching of circuits containing inductors, capacitors, and can inflict serious damages on machinery and other equipments. In this study, the electrical properties of ZnO based varistor doped with different additives are investigated in conjunction with the photothermal properties. The wavelength of incident light is kept in the range from 300 to 800 nm and the PPE spectrum with reference to the doping level, sintering conditions is discussed. The energy band-gap or shortly as band-gap is determined from the plot (ρhυ)2 vs hυ. The band-gap is reduced from 3.2 eV (pure ZnO) to about 1.9 eV for single additive MnO2 or when it is used with the combination of other additives. The steepness factors σA (in A-region), and σB (in B-region), which characterize the slope of exponential optical absorption are discussed in conjunction with the band-gap which give the information about the disordering of the structure. It was also found that the value of band-gap slightly increases or decreases in 13 material systems in the range of 0.03 to 0.05 eV. It was found that the secondary phases such as Bi4Ti3O12, Zn2TiO4, Zn7Sb2O12 are grain suppressors. The maximum and minimum relative densities for all systems in this study are about 96 %, 78 %, respectively. The maximum grain size was found to be 82 μm when ZnO was doped with MnO2, Co3O4, Bi2O3, TiO2 for 3 hour sintering time. It was found that the TiO2 is a strong grain enhancer; Sb2O3 is a strong grain suppressor upto certain doping level. SEM and EDX results show that the additives Bi2O3, Y2O3, Er2O3, Dy2O3 and Pr6O11 are segregated at the grain boundaries and at the triple point junctions. EDX analysis show that the Co, Mn, Ti ions are distributed on the grain surfaces as well as grain boundaries. Current-voltage characteristics of the varistor show that the varistor voltage increases with the decrease of grain size. The value of barrier height increases with the increase of the nonlinear coefficient and vice versa but it deviates in some cases. The value of band-gap decreases due to the increase in the structural disordering and increases due to the decrease in the structural disordering. It is found that the increase or decrease in the band-gap ranges from 0.03 to 0.05 eV in all cases but this ranges from 0.1 to 0.3 eV only for xBi2O3 and xPr6O11 doped ZnO system. The change in the value of the band- gap in conjunction with the nonlinearity of the doped ZnO can be categorized in four cases as both band-gap and nonlinearity increases in system 5, band-gap decreases and nonlinearity increases in system 2, system 10 and system 11, band-gap increases and nonlinearity decreases in system 6, system 8 and system 13, both band-gap and nonlinearity decreases in system 7, system 9, and system 12. System 12 which is Bi2O3, TiO2, Co3O4, doped ZnO with and without Sb2O3 at different sintering temperatures is the best system found in which both band-gap and nonlinearity decreases having the maximum value of nonlinearity that is 7.9 at the sintering temperature of 1210 oC for one hour sintering time with 0.02 mol% Sb2O3. The second best system found in the project is System 13 which is Bi2O3, TiO2, MnO2, doped ZnO with and without Sb2O3 at different sintering temperatures in which band-gap increases and nonlinearity decreases with the maximum value of nonlinearity that is 18.6 at the sintering temperature of 1180 oC for one hour sintering time with Sb2O3.